PENGARUH SELEKSI KARYAWAN DAN KOMUNIKASI TERHADAP PRESTASI KERJA KARYWAN PADA PT. PELABUHAN INDONESIA I (PERSERO) MEDAN - Panjaitan, Desielsa; Ritonga, Sinar (UNIKA Santo Thomas, 2018)
PT. Pelabuhan Indonesia I (Persero) Medan is one of the State-Owned Enterprises (BUMN) in the form of company companies engaged in services, especially port services in Indonesia. Communication within the company is not good because there is still insufficient communication media in the company. As a result, employee performance in 2015-2017 experienced fluctuations. From the description, the research problem was formulated (1) how employee selection and communication on the work performance of PT. Indonesian Port I (Persero) Medan? (2) how much influence the selection of employees on employee performance at PT. Indonesian Port I (Persero) Medan? (3) how much influence communication has on employee work performance at PT. Indonesian Port I (Persero) Medan? (4) how much influence does employee selection and communication have on employee work performance at PT. Indonesian Port I (Persero) Medan. This study aims to determine the effect of employee selection and communication on employee performance at PT. Indonesian Port I (Persero) Medan. The benefit of research is to provide information material to the leadership regarding the influence of employee selection and communication on employee performance. The study population was all employees in the HR department at PT. Pelabuhan Indonesia I (Persero) Medan 123 people. The data needed is collected through interviews, questionnaires and documentation studies. The data analysis technique used is multiple linear regression equation, F test and t test.